1999
DOI: 10.1074/jbc.274.21.14573
|View full text |Cite
|
Sign up to set email alerts
|

An Arginine Residue Is Essential for Stretching and Binding of the Substrate on UDP-glucose-4-epimerase from Escherichia coli

Abstract: In the previous paper we demonstrated that uridine-5-␤-1-(5-sulfonic acid) naphthylamidate (UDPAmNS) is a stacked and quenched fluorophore that shows severalfold enhancement of fluorescence in a stretched conformation. UDPAmNS was found to be a powerful competitive inhibitor (K i ‫؍‬ 0.2 mM) for UDP-glucose-4-epimerase from Escherichia coli. This active sitedirected fluorophore assumed a stretched conformation on the enzyme surface, as was evidenced by full enhancement of fluorescence in saturating enzyme conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Marked fluorescence enhancements have been observed for a more extended configuration induced by the nucleotide-binding site of a protein, due to hindrance of this chromophore-base quenching interaction. Several proteins have been studied in this way, such as RNA polymerase (14), UDP-glucose 4-epimerase (15), and a large number of dehydrogenases using NAD or etheno-NAD as probes (16). Draganescu et al (17) have described the binding of BODIPY FL GTP-␥-S and other nonfluorescent ␥-phosphatelinked analogs to Fhit, a member of the histidine triad superfamily of nucleotide-binding proteins involved in tumor suppression.…”
mentioning
confidence: 99%
“…Marked fluorescence enhancements have been observed for a more extended configuration induced by the nucleotide-binding site of a protein, due to hindrance of this chromophore-base quenching interaction. Several proteins have been studied in this way, such as RNA polymerase (14), UDP-glucose 4-epimerase (15), and a large number of dehydrogenases using NAD or etheno-NAD as probes (16). Draganescu et al (17) have described the binding of BODIPY FL GTP-␥-S and other nonfluorescent ␥-phosphatelinked analogs to Fhit, a member of the histidine triad superfamily of nucleotide-binding proteins involved in tumor suppression.…”
mentioning
confidence: 99%
“…Folding studies can also be facilitated by using these probes to monitor the generation of ligand binding site during the folding process. In the following paper usefulness of UDPAmNS as a quenched fluorophore will be demonstrated taking UDPglucose-4-epimerase from Escherichia coli as the target enzyme (32).…”
Section: Discussionmentioning
confidence: 99%
“…ATPAmNS, GTPAmNS, and PPAmNS failed to show any significant enhancement under identical conditions. Most of the subsequent spectroscopic work reported here was carried out with UDPAmNS, because this molecule showed maximum enhancement of fluorescence and was also used as the probe for our subsequent study with UDPgalactose-4-epimerase, as reported in the following paper (32).…”
Section: H Nmr Spectroscopy-thementioning
confidence: 99%
“…Compared with the ϳ15-fold increase in fluorescence of NADH bound to deoxyhypusine synthase, the increase in peak intensity in 90% tetrahydrofuran was only 3-fold that of the same concentration of NADH in buffer, suggesting that there may be additional factors affecting the enhancement of fluorescence emission. One is the relief of both static and collisional quenching between the adenine and dihydronicotinamide moieties that occurs in the "closed" conformation of NADH in aqueous solution, which has been cited by Weber and others (20,21,35,36). When bound to an enzyme, the NADH generally assumes a more "open" conformation, increasing the distance between the two ring systems and thus increasing the fluorescence emission (20).…”
Section: Figmentioning
confidence: 99%